Phenolic, tannin, antioxidant, color, and sensory attributes of Barhi date (Phoenix dactylifera) fruit stored in modified atmosphere packages. Issue 5 (25th July 2018) - Alsawmahi, Omer N.; Al‐Juhaimi, Fahad; Alhamdan, Abdullah M.; Ghafoor, Kashif; Adiamo, Oladipupo Q.; Mohamed Ahmed, Isam A.; Hassan, Bakri H.; Ehmed, Kheled A.; Babiker, Elfadil E.; Abdelkarim, Diaeldin; Younis, Mahmoud; Alashmawe, Nasser
Abstract: Modified atmosphere packaging (MAP) was evaluated for total phenolic contents (TPC), antioxidant, tannin, color, and sensory properties of fresh Barhi dates. Polypropylene (PP) and polyethylene (PE) with different perforations (0 [H0], 50 µm [H3], 100 µm [H6], and 150 µm [H9]) were evaluated for storing fresh Barhi dates for up to 45 days at 1 to 25°C temperature. MAP significantly ( p  ≤ .05) affected the properties investigated as compared to control. PE dates have higher ( p  ≤ .05) TPC than PP dates, whereas other properties remained largely unaffected by packaging material. TPC and antioxidant activity were higher ( p  ≤ .05) in H0 treated dates. H9 perforated packaged dates exhibited higher ( p  ≤ .05) tannin contents, better sensory and color attributes. Barhi dates exhibited fresh‐like quality and better antioxidant properties at low storage temperature (5°C) for up to 2 weeks' storage and similar was verified by principal component analysis using HJ plots where storage temperature was observed as major factor. Practical applications: Modified atmosphere packaging or MAP is an emerging technique for preserving fresh fruits and vegetables and it is being studied extensively for different fresh commodities in order to preserve their fresh like characteristics. There is a need to study MAP effects on storing new and economically important fruits such as Barhi dates which have shorter life in early stages of maturity but cherished when freshly harvested due to various health benefits and characteristic taste and quality. MAP was effectively tested and applied for preserving Barhi dates and MAP variables were evaluated in order to find the best packaging conditions which may ensure maximum consumer benefits and date quality.